Liquid chromatography–tandem mass spectrometry analysis of aristolochic acids in soil samples collected from Serbia: Link to Balkan endemic nephropathy. (29th October 2019) - Chan, Chi‐Kong; Chan, K.K. Jason; Pavlović, Nikola M.; Chan, Wan
Abstract : Rationale: Over the past six decades, residents of farming villages in multiple countries of the Balkan peninsula have been suffering from a unique type of chronic renal disease, Balkan endemic nephropathy (BEN). It was speculated that environmental pollution by aristolochic acids (AAs) produced naturally by Aristolochia clematitis L., a weed that grows in the area, was causing the disease. However, the human exposure pathway to this class of phytotoxin remains obscure. Knowledge of the sink and stability of AAs in the environment would assist in the formulation of policy reducing exposure risk. Methods: Using our newly developed liquid chromatography/tandem mass spectrometry method of high sensitivity and selectivity, we analysed over 130 soil samples collected from cultivation fields in southern Serbia for the presence of AAs. The environmental stability of AAs was also investigated by incubating soil samples spiked with AAs at various temperatures. Results: The analysis detected AA‐I in over two‐fifths of the tested samples at sub‐μg/kg to μg/kg levels, with higher concentrations observed in more acidic farmland soil. Furthermore, analysis of soil samples incubated at various temperatures revealed half‐lives of over 2 months, indicating that AAs are relatively resistant to degradation. Conclusions: Cultivation soil in southern Serbia is being extensively contaminated with AAs released from the decomposition of A. clematitis weeds. Since AAs are resistant to degradation, it is possible that AAs could have been taken up by root absorption and transported to the edible part of food crops. Prolonged exposure to AA‐contaminated food grown from polluted soil could be one of the main aetiological mechanisms of BEN observed in the area.